Algae digestate biostimulants as an innovative solution for food system sustainability and productivity improvement - Skapste, Inese; Vircava, Ilze; Skutele, Kristiana; Žaimis, Uldis; Grinberga-Zalite, Gunta; Zvirbule, Andra (Frontiers in Sustainable Food Systems, 2025)
Europe’s food system currently faces significant challenges, including demographic changes, high dependence on synthetic fertilizers, and growing climate change impacts. Aligned with the goals of the European Green Deal and the Farm to Fork policy, this study aims to explore the potential of an algal digestate-based biostimulant to enhance crop productivity and reduce reliance on synthetic fertilizers in sustainable agricultural systems. A vegetation tray trial was conducted using three cover crops representative of palustrine species in the Baltic Sea region: lettuce, radish, and spinach. The effects of full and reduced mineral fertilization with and without algal biostimulant supplementation were assessed. The results showed that using the biostimulant, especially at a 6% application rate, could partially compensate for reduced nutrient input. This approach exceeded the yields of conventional full-strength fertilization while improving soil health and minimizing fertilizer input. Statistical analyses (ANOVA and Tukey HSD) confirmed significant yield increases for treatments with the biostimulant, particularly under nutrient-limited conditions. These results suggest that algal biostimulants have the potential to advance sustainable and resilient food production systems in Europe.